Korelacje pomiędzy ideologią „trzeciej drogi” a redefinicją konfliktu w polskim życiu politycznym - Niebylski, Michał (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
The aim of this article is to study the philosophical, ideological and political roots of the Third Way concept. The analysis of these aspects should capture the genuine sources of the new faces of European social democracy and prove the thesis that this model is influential in West Europe as well as in Poland. The article asks the question: is the Third Way a political ideology with its own distinctive ‘core’, a loose fusion of different ideologies, or a strategy within an ideological tradition? Moreover, the article is an attempt to examine on what level the formula of the Third Way assume ‘going out’ of the disputes between the left and the right. Finally, the paper examines the correlation between politics of Third Way and the redefinition of political conflict in the Poland after 1989.